Análisis de la interpretación del semáforo alimenticio en los productos de bebidas no alcohólicas en la línea de maltas en la escuela particular Cayetano Tarruell de la parroquia Ximena cantón Guayaquil año 2016 - Campi Saona, Edith Desiree (2016)
Pony Malta is a vitaminized energy drink product that delivers nutrients for physical growth and development. As the nutritional traffic light indicator was placed on mass consumption products’ tags, the Ministry of Public Health and the Ministry of Education consequently presented a ban on selling this energy drink product within educational institutions. This caused parents not to include these types of energy drinks in their children’s lunch boxes. Since this beverage is heavily dependent on the “school-aged” consumption, Pony Malta Plus (which contains a “yellow light” on the nutritional traffic light indicator for moderate sugar amount) was considered for launch. If allowed to be commercialized within the school-aged market, the original product’s consumption should be reconsidered, since it has not been sold in educational establishments in over a year……